Development of Science Literacy-Based Teaching Materials on Soil Formation Process and Soil Building Components - Nisa, Hayatun; Febriyani Putri, Rizky; Hafizah, Ellyna (Journal of World Science, 2023)
The learning process motivates the development of scientific literacy-based teaching materials on the material of soil formation processes and soil constituent components. So far, it has only used teaching materials in school textbooks. The purpose of the researchers in carrying out this development was to find out 1) the validity of scientific literacy-based teaching materials on the process of soil formation and soil constituents, (2) the practicality of teaching materials, and (3) the effectiveness of teaching materials. Development of teaching materials using the 4D model (define, design, develop and disseminate). The instruments implemented in the research include learning achievement tests, student response questionnaires, and teaching material validation sheets. The research validated scientific literacy-based teaching materials, showing very valid criteria by obtaining a score of 3.70. The learning outcomes test on this teaching material was also very valid, with a value of 3.51. The results of the practicality of teaching materials obtained a value of 70.85% which was indicated by practical criteria. Teaching materials based on scientific literacy were also declared effective by obtaining an n-gain of 0.91 with high criteria. From these results, the advanced scientific literacy-based teaching materials can be implemented as teaching materials because the test results are declared feasible and valid.